Strategi Brand Kosmetik Lokal untuk Pengguna Pemula: Penyediaan Varian, Penetapan Harga, dan Penekanan Risiko Efek Samping - Darmawan, Didit; Mufidah, Indah (Lembaga Pengembangan Kinerja Dosen, 2026)
This literature study aims to analyze the strategies of local cosmetic brands in providing product variants for different skin types, setting affordable prices for the teenage segment, and minimizing side effect risks to increase purchase intention among beginner users. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that complete product variants enable beginner users to find products suitable for their skin conditions, reducing confusion and increasing confidence. Affordable prices are crucial for the teenage segment with limited budgets, allowing them to try products without excessive financial burden. Minimizing side effect risks through safe formulations, dermatological testing, ingredient transparency, and usage education builds a sense of security essential for beginner users. These three strategies are interconnected and collectively create a foundation of trust that drives purchase intention. Beginner users who feel their needs are understood, products are affordable, and risks are minimal will be more motivated to purchase and have the potential to become long-term loyal customers. This study contributes theoretically to enriching cosmetic marketing literature with a teenage and beginner user segmentation perspective and practically provides foundations for local brands in designing products, pricing strategies, and safety communications targeting this segment.